40-min nap opportunity attenuates heart rate and perceived exertion and improves physical specific abilities in elite basketball players - Souabni, M.; Hammouda, O.; Souabni, M. J.; Romdhani, M.; Driss, T. (Research in Sports Medicine, 2023)
The effect of a 40-min nap opportunity on physiological responses and specific abilities was investigated. Twelve high-level professional basketball players (26.33±5.2 years; 193.17±7.1 m; 87.48±11.2 kg) undertook randomly 40-min nap opportunity (NAP) and control condition (CON). Wellness (Hooper Index) and Epworth Sleepiness Scale (ESS) were measured before and after both conditions. Defensive (DA) and offensive (OA) agility and upper body power (UBP) were assessed after both conditions. Shooting skill (SST) performance was evaluated prior and after a fatiguing task (FT). Heart rate (HR) and rating of perceived exertion (RPE) were recorded during SST-test, FT and SST-retest. ESS, Hooper`s stress and fatigue score were significantly lower after nap compared to those before nap (0.009 = p = 0.03). Better performance was obtained in NAP compared to CON condition for DA, OA and UBP (0.0005 = p = 0.02). SST performance was significantly higher in NAP compared to CON in the retest session (p = 0.003, delta = 20.2%). The improved performance was associated with significant lower HRpeak (p = 0.01, delta = 5.25%) and RPE (p = 0.003, delta = 15.12%). In conclusion, NAP reduced sleepiness and stress and fatigue and enhances physical outcomes of specific skills in elite basketball players.